A new Dienerian (Early Triassic) brachiopod fauna from South China and implications for biotic recovery after the Permian–Triassic extinction. (5th July 2017) - Wang, Fengyu; Chen, Jing; Dai, Xu; Song, Haijun
Abstract: Brachiopods suffered severe extinction during the Permian–Triassic crisis, such that their diversity dropped to extremely low levels in the Early Triassic. Here we describe a new brachiopod fauna from the Dienerian of Lichuan, South China. This fauna consists of three monospecific genera, including one new genus and one new species: Lichuanorelloides lichuanensis gen. et sp. nov., Lissorhynchia sp. and Crurithyris sp. These brachiopods co‐occur with the ammonoids Ussuridiscus, Jieshaniceras, Hubeitoceras and Vishnuites, suggesting an early Dienerian age. The geographical distribution of brachiopods in family Norellidae during the Early Triassic suggests that a migration took place towards higher latitudes, which may have been caused by the extreme climate warming that prevailed during the Dienerian.